2013
DOI: 10.4103/2152-7806.120778
|View full text |Cite
|
Sign up to set email alerts
|

Primary elective spine arthrodesis: Audit of institutional cross matched to transfused (C/T) ratio to develop blood product ordering guidelines

Abstract: Background:Currently, there are no uniform guidelines regarding the appropriate amount of blood products ordered prior to spine surgery. Here, we audited our own institution's practices along with preoperative variables that contributed to perioperative transfusion requirements for elective spinal arthrodesis.Methods:This study utilized a single institution retrospective chart review of patients undergoing elective spinal fusion over a 2 year period. The cross matched to transfused (C/T) ratio was utilized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Although that study had a much smaller sample size they also included all levels of the spine. Our analysis showed similar results to those presented by Alam et al [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although that study had a much smaller sample size they also included all levels of the spine. Our analysis showed similar results to those presented by Alam et al [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although lower than transfusion need in lumbar fusion, our results showed that the rate of transfusion was highest (9.3%) in the posterior cervical spine fusion patients in comparison to a much lower rate in patient undergoing ACDF (0.77%). The low transfusion rate in ACDF has been reported in the literature [ 17 18 ]. Alam et al [ 18 ] demonstrated that posterior fusion was at increased risk of requiring transfusion in comparison to anterior procedure in the cervical spine which is consistent with the results presented in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This figure is grossly overestimated and there is evidence that blood packs are being wasted due to this lack of standardization 9.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a published audit of our own institution's practices along with preoperative variables that contributed to perioperative transfusion requirements for elective spinal arthrodesis highlighted an unacceptably high C/T ratio and based on univariate analysis, recommending two units packed cells to be arranged for patients with preoperative hemoglobin levels <9 g/dl, trauma, and adult idiopathic scoliosis (AIS) cases, or where more than two levels are being decompressed and/or arthrodesed, and for the remainder of the cases, a group and hold policy should be sufficient. [1] Hence, a prospective validation of this individual patient-based blood ordering protocol for elective spine arthrodesis highlights implementing our recommended protocol reduced the crossmatch to transfusion ratio from 4.02 to 1.74 and an overall cost reduction of 30%. [20] Other papers have similarly addressed the cost-effectiveness of a protocol-based arrangement of blood products for elective surgeries, and the concept of maximum surgical blood order schedule (MSBOS) was previously developed and implemented in other developed countries,[8] which resulted in significant cost reduction while changing practices for “routinely” or “unnecessarily” ordering blood.…”
Section: Discussionmentioning
confidence: 99%